Culture and authenticity - Lindholm, Charles (Oxford Blackwell publishing, 2008)
Authenticity is taken-for-granted as an absolute value in contemporary life. In Culture and Authenticity, Charles Lindholm calls upon anthropological case studies from different cultures, historical material, and comparative philosophy, to explore how notions of authenticity develop, what forms it takes, and how it changes over time. - Examines the idea of authenticity and its role in modern culture- Explores societys preoccupation with authenticity and the search for real experiences- Looks at how the concept of authenticity intersects with questions about religion, ethnicity, and race- Investigates authenticity in the context of fields such as dance, cuisine, travel, and the modern marketplace